Strategi Manajemen Konflik Dalam Meningkatkan Efektivitas Organisasi: Indonesian - Al Candra, Muhamad Rohid; Arifin, Fadhilah Rabbani; Widyadhana, Rajendra Aryasatya (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
Conflict is an unavoidable phenomenon in an organization, especially when various individuals with diverse backgrounds, interests, and goals interact with each other. This study aims to analyze effective conflict management strategies in improving organizational effectiveness. This study uses a qualitative descriptive method with a case study approach in a particular organization. Data were collected through in-depth interviews, observations, and document analysis to understand the patterns of conflict that occur, the conflict resolution strategies applied, and their impact on organizational effectiveness. The results of the study indicate that conflict in organizations can be managed effectively through a collaborative approach, open communication, and mediation involving all related parties. This strategy is able to improve teamwork, strengthen relationships between individuals, and support the achievement of organizational goals. However, this study also found that a lack of effective communication and an inappropriate approach to dealing with conflict can worsen the situation, reduce productivity, and create dissatisfaction among employees. As a recommendation, organizations are advised to adopt conflict management strategies based on communication training, strengthening adaptive leadership, and developing internal policies that support constructive conflict resolution. The implementation of this strategy is expected to create a harmonious work environment and improve overall organizational effectiveness.